What Is the Role of AI in Home Health Monitoring? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2020)
The integration of artificial intelligence (AI) into home health monitoring is revolutionizing healthcare delivery, offering unprecedented opportunities for ...
Keywords: Telemedicine and Digital Health; Health; Monitoring; Artificial Intelligence; Machine Learning; Healthcare